Performance analysis of packet scheduling algorithm for femtocell-macrocell scenario in LTE network / Muhammad Naqiuddin Sahrani, Darmawaty Mohd Ali and Azlina Idris - Sahrani, Muhammad Naqiuddin; Mohd Ali, Darmawaty; Idris, Azlina (Universiti Teknologi MARA, 2019)
The increasing number of users has led to various challenging issues especially when providing coverage to the users in the building. The indoor coverage deteriorates since the signal cannot pass through the wall completely. The coverage signal will become weaker and affect the Quality of Service to the customers. Operators have tried to overcome this problem by providing small cells (femtocells) inside the building. In this paper, we have investigated the performance of packet scheduling algorithms; Proportional Fairness (PF), Round Robin (RR), Priority Set (PSS), Blind Equal Throughput (BET) and Maximum Throughput (MT) in the LTE environment where a dual stripe block type apartment is included in the network topology. Each apartment is assumed to have two femtocells where each cell is serving five customers. Meanwhile, the number of users in the Macrocell is varied between 50 to 200. Three types of services are delivered during the simulation which are VoIP, video and FTP. The simulations results are presented in the terms of throughput and delay. It can be concluded that PF and RR algorithms are the most compatible to be deployed in the Macrocell-Femtocell environment.